An integrated study of low resistivity hydrocarbon zones : a study of the two "dual resistivity" gas reservoirs onshore Mozambique Basin - Altermann, Wladyslaw, 1954- (University of Pretoria, 2015)
Thesis (PhD (Geology))--University of Pretoria, 2015.